Analysis of influencing factors on Turner syndrome combined with autoimmune thyroid disease - Yingmei Cen; Wei Wei; Yinchun Huang; Yiying Qi; Gendie E. Lash; Li Li (Frontiers in Endocrinology)
BackgroundAutoimmune thyroid disease (AITD) is the most common autoimmune disease in patients with Turner Syndrome (TS). There is a high prevalence of AITD in TS patients, it has an early age of onset and can present as severe thyroid dysfunction. The specific etiology of AITD in TS is not clear and may be associated with sex chromosome-related genetic defects, immune dysfunction, or sex hormone imbalance due to ovarian insufficiency. The aim of this study was to investigate the prevalence and related influencing factors of AITD in Chinese patients with TS.MethodsIn total 63 female patients aged 14–32 diagnosed with TS received titer of thyroid autoantibodies and thyroid function examinations, including thyroid stimulating hormone (TSH), free tetraiodothyronine (FT4), free triiodothyronine (FT3), total thyroxine (TT4), total triiodothyronine (TT3), thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). The effects of age, body mass index (BMI), karyotype, fasting insulin, blood lipids and other factors that may affect thyroid function were analyzed, and the possible risk factors associated with AITD in TS patients explored.ResultsOf the 63 TS patients, 24 (38.10%) had normal thyroid function and 39 (61.90%) patients had TgAb and/or TPOAb. Among the 39 women with positive thyroid autoantibodies, 10 had abnormal thyroid function, including 3 with hyperthyroidism and 7 with hypothyroidism. Patients with isochromosome X had an increased risk of developing AITD.ConclusionsThe risk of AITD with TS correlates with the chromosomal karyotype, patients with isochromosome X have an increased risk of AITD. Patients with positive thyroid autoantibodies have a higher risk of thyroid dysfunction.